2015
DOI: 10.9734/bjmmr/2015/14845
|View full text |Cite
|
Sign up to set email alerts
|

Recurring Outbreaks of an Infection Apparently Targeting Immune Function, and Consequent Unprecedented Growth in Medical Admission and Costs in the United Kingdom: A Review

Abstract: Background:The National Health Service (NHS) in the UK has been beset by unprecedented growth in emergency admissions to hospital which are specifically medical in nature, while surgical and trauma admissions are only showing the level of low growth expected from demographic change, or what is called the ageing population. There has never been an adequate explanation for this dichotomy. An Infectious Basis: The proposed infectious basis rests upon the observation that growth in medical admissions occurs in spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 144 publications
(362 reference statements)
2
45
0
Order By: Relevance
“…When this point is reached, inevitable trade-offs between quality and cost of care would have to be made however implicit and undesirable this may be (Jones 2011). For example, it is commonly observed that bed occupancy greater than 85% leads to increased risk of hospital acquired infections, serious errors and higher mortality (Jones 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this point is reached, inevitable trade-offs between quality and cost of care would have to be made however implicit and undesirable this may be (Jones 2011). For example, it is commonly observed that bed occupancy greater than 85% leads to increased risk of hospital acquired infections, serious errors and higher mortality (Jones 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Bed occupancy greater than 85% is a surrogate marker of reduced staff per patient ratios and is an indicator of a cost efficient but under resourced service (Jones 2011(Jones , 2015(Jones , 2016. Jones et al reported a close correlation between annual Summary Hospital-level Mortality Indicator (SHMI) and inpatient bed occupancy above 85% (Jones 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The curious observation is that these saw-tooth features have been identified across the whole of Europe, Australia, New Zealand, and in the counties of Arizona (USA) [36][37][38] and also simultaneously occur for the associated medical hospital admissions arising from the nearness to death effect. [39][40][41][42][43] Figure 2 demonstrated clear saw-tooth patterns for a local authority having a simple population structure.…”
Section: International Behaviormentioning
confidence: 99%
“…The unique feature of these outbreaks is that various measures of morbidity and mortality all rise for a 12-month period before reverting to baseline levels [1][2][3][4][5][6]. These outbreaks can be traced back to the 1950's, but presumably occur prior to this [7]. The effect upon deaths has been documented in the UK, across Europe, Australia, New Zealand, USA [7][8][9][10], and Canada (unpublished), and occurs in sub-local authority small areas [4,11,12].…”
mentioning
confidence: 99%
“…These outbreaks can be traced back to the 1950's, but presumably occur prior to this [7]. The effect upon deaths has been documented in the UK, across Europe, Australia, New Zealand, USA [7][8][9][10], and Canada (unpublished), and occurs in sub-local authority small areas [4,11,12]. The simplest way of detecting these unique events is to utilize a running (moving) 12-month total of deaths.…”
mentioning
confidence: 99%